Perancangan Sistem Kontrol Penerbangan Fuzzy untuk Stabilitas Drone Menggunakan Matlab/Simulink - Rahman, Muhammad Arif; Widhiada, I Wayan; Suryawan, Anak Agung Adhi (Teknik Desain Mekanika; Vol 10 No 4 (2022): Oktober 2022 : Teknik Desain Mekanika, 2022)
Abstract As time goes by, the technology development has shown a very rapid growth. The discovery of drones or unmanned aerial vehicles (UAV) is one of the developed examples of technology that has helped humans finishes many task. This study will discuss fuzzy control to stabilize the error and attitude of the quadcopter when it gets a load and disturbance so that the drone will not fall or remain stable. This research was conducted to create a quadcopter model and provide a fuzzy controller which then simulated and applied to the existing quadcopter. According to the data from experiments without and using fuzzy control, it can be concluded that fuzzy control that has been applied to drones can improve the condition of drones that experience errors. This is caused by the error signal that has been obtained from the drone sensor has been fuzzified by fuzzy logic control. The flight graphs show that using fuzzy controls resulting a better flight outcome than the experiments without using fuzzy. Without control, drone do not reach the destination position and fail to correct errors that cause the drone to fall in only 3s of flight time. Keywords : drone, fuzzy logic, control, error